Mesenchymal Tumors of the Liver: An Update Review - Joon Hyuk Choi; Swan N. Thung (Biomedicines)
Hepatic mesenchymal tumors (HMTs) are non-epithelial benign and malignant tumors with or without specific mesenchymal cell differentiation. They are relatively uncommon. Except for mesenchymal hamartoma, calcified nested stromal–epithelial tumor, and embryonal sarcoma, most mesenchymal lesions are not specific to the liver. Pathologists face challenges in diagnosing HMTs due to their diverse morphologies and phenotypic variations. Accurate diagnosis is critical for directing appropriate patient care and predicting outcomes. This review focuses on mesenchymal tumors with a relative predilection for the liver, including vascular and non-vascular mesenchymal neoplasms. It provides a thorough and up-to-date overview, concentrating on clinical and pathological features, differential diagnosis, and diagnostic approaches.